Impact of COVID-19 pandemic on Indian economy - Narayanappa, Sharada; Boyanagari, Vamsi Krishna; Uthkarsh, Pallavi Sarji (International Journal Of Community Medicine And Public Health, 2022)
The Coronavirus disease 2019 (COVID-19) pandemic has emerged as the most challenging biological disaster of the 21st century. The sudden onset of pandemic in the background of unpreparedness and the lockdown and social distancing measures has impacted the economies of not only the less developed but also the well-developed countries. The objective of this paper is to examine the economic impact of the COVID-19 pandemic on the various sectors of the Indian economy. The data has been collected from the start of the pandemic till the second week of May 2021. The results of the study show that the policy measures taken to contain the pandemic resulted in a severe crunch in the Indian economy. The GDP growth rate recorded a negative figure, the manufacturing sector and contact- intensive hospitality service sectors, domestic and international trade had to shut down and suffered losses like never before. Agriculture, Information technology and software services sector remained resilient and sustained the economy. Migrants had to revert back to their hometowns in search of alternate jobs, unemployment was at its highest during the lockdown in 2020. Continued policy measures and monetary support are needed to cope with the economic impact of COVID-19 in the backdrop of an unprecedented forecast.